Validation of ELPO-PT: A Risk Assessment Scale for Surgical Positioning Injuries in the Portuguese Context - Andreia Salvini; Elsa Silva; Carmen Passos; Tânia Manuel; Camila Moraes; Clementina Sousa; Paulo Alves (Nursing Reports)
Background/Objectives: Surgical procedures carry inherent risks, including injuries from surgical positioning, which impact patient safety and healthcare quality. An instrument to assess and prevent these injuries is essential. This study aimed to validate and culturally adapt the ELPO-PT for the Portuguese population to ensure its applicability and effectiveness in assessing the risk of injury from surgical positioning. Methods: A validation study was conducted with 126 adult patients undergoing surgical procedures at a central hospital in northern Portugal. Statistical analyses, including the calculation of Cronbach’s alpha coefficient, assessed the internal reliability of the scale. Additionally, sensitivity and specificity analyses evaluated the ELPO-PT’s diagnostic accuracy in identifying patients at risk of developing positioning-related injuries. Results: The validation showed a Cronbach’s alpha coefficient of 0.782, indicating reasonable internal reliability. Sensitivity analysis revealed an 85% accuracy rate in identifying patients at risk of positioning injuries, while specificity analysis demonstrated a 90% accuracy rate for patients not at risk. Conclusions: The ELPO-PT is a valid and reliable instrument for aiding nurses in clinical decision-making, with significant sensitivity and specificity in identifying the risk of positioning-related injuries, including pressure ulcers, in adult patients during the intraoperative period. Its implementation is expected to be beneficial in healthcare settings, contributing to the prevention of complications associated with surgical positioning.